Valorising and Creating Access to Innovative Medicines in the European Union - Annemans, Lieven; Cleemput, Irina; Hulstaert, Frank; Simoens, Steven (Frontiers in Pharmacology, 2011)
This Perspective describes (a) the current situation, (b) challenges and initiatives, (c) and formulates recommendations to valorize and create access to innovative medicines in the EU. We are currently still far away from optimal assessment of value for money in the EU. On the one hand, valorizing innovative medicines involves a local appraisal by health technology assessment bodies and competent authorities of the value for money, the budget impact and the local medical need that can be filled with new medicines. Therefore, local priorities and national health care policy environments should be reflected in the processes and criteria used for assessing value for money and ultimately for reimbursement decisions. On the other hand, a pan-European assessment of both relative effectiveness and medical need (including general ethical and social considerations) should be envisaged in order to feed part of the data needed for the local decisions in an efficient way. This could be the task of the European Medicines Agency, health technology assessment bodies and competent authorities together.